The Role of Information and Communication Technology on Service Trade : Case Study of Indonesia's Export to ASEAN Countries - Dyah Titis Kusuma Wardani; Faiza Husnayeni Nahar; Hairunnas Hairunnas (MediaTrend, 2020)
This study aims to analyze the impact of Information and Communication Technology (ICT) on bilateral trade in service between Indonesia and its ASEAN trading partners. The sample is bilateral export in service between Indonesia and 9 ASEAN countries such as Malaysia, Philippines, Singapore, Thailand, Brunei Darussalam, Vietnam, Myanmar, Laos and Cambodia. The total trade in service data is based on UN-Comtrade. It consists of service products that are coded in Standard International Trade Classification (SITC). This study uses the gravity model framework of data panel from 2005 to 2017 with random effect model is analyzed using Generalized Least Square. Based on the regression analysis, results show that sub-index of ICT Development Index (IDI) such as mobile-cellular telephone subscriptions per 100 inhabitants which represents technology development, has a positive and significant impact on Indonesia’s service export to ASEAN countries. Other variables such as GDP and distance also have significant effect on Indonesia’s export in service. GDP reporter, GDP partners and common language have positive and significant effect on Indonesia’s export in service. Furthermore, distance has a negative and significant effect on Indonesia’s export in service. These results are in line with Gravity model theory. In addition, these results are expected to be strong enough for the specifications of alternative models and estimation methods. Based on these results, some expected trade policy recommendation related to trade in service and telecommunication particularly trade between Indonesia and ASEAN countries can be formulated. For instance, to strengthen Indonesia’s networking and infrastructure of telecommunication in ASEAN countries. To build more Base Transceiver Station (BTS) located in trading partners in ASEAN. Telin Singapore established by Telkom Indonesia is officially established in 2007 and is the first Telkom footprint in international business. Since Singapore is Indonesia’s trading partner which has the highest of ICT Development Index among other ASEAN countries, the Indonesian government need to continue the implementation of Information and Communication Joint Committee Indonesia-Singapore.